PENGARUH KEPEMIMPINAN DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA CV ASEP RESIN CORPS - Surya Negara, Riky Hermawan; Prasetyo, Hendri (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the influence of leadership and discipline on employee performance on CV Asep Resin Corps both partially and simultaneously. The research method used is a quantitative method with an associative approach. The sampling technique used is a saturated sampling technique, which uses a sample of 56 respondents from the entire population. The data analysis techniques used are instrument test, classical assumperusahaanion test, linear regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis test. This is evidenced by the results of the leadership hypothesis test obtained a calculated t value of 2,264 > t table 1,673 andreinforced by the value of ρ value < Sig.0.05 or significance value < 0.05 (0.000< 0.05) and discipline obtained a calculated t value of 2,436 > ttable 1.673 and reinforced by the value of ρ value < Sig.0.05 or significance value < 0.05 (0.000< 0.05). The results of leadership and discipline research simultaneously have a significant effect on employee performance on CV Asep Resin Corps shown by the multiple linear regression regression equation Y = 12.347 + 0.334X1 + 0.357X2. This is evidenced by the results of the hypothesis test simultaneously obtained the calculated F value (24.149 > Ftable 3.17) and reinforced by a significance value of < 0.00 (0.000 < 0.05). The results of the coefficient of determination of leadership and discipline variables have an influence of 47.7% on employee performance on CV Asep Resin Corps. ThusH0 is acceperusahaaned and H3 is rejected. This means that there is a simultaneous significant influence between leadership (X1) and discipline (X2) on employee performance (Y).